Answer and explanation:
Given :
![f(x)=y=(3x)/(8+x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i82op9k5vmc80xqg72ta2lyhainy9t68dd.png)
To find : Arrange the equations in the correct sequence to find the inverse of f(x) ?
Solution :
Writing step by step to find inverse,
Step 1 - Interchange y with x,
![x=(3y)/(8+y)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dat5wc2oes1ee03sm2o34vlrtm3xl54egf.png)
Step 2 - Cross multiply,
![x(8+y)=3y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/55omk7d6jm9mn2ka3pab43yco48hrlda45.png)
Step 3 - Apply distributive property,
![8x+xy=3y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tfdojf4er7mz1i3olz2jcag7ed6i87hz26.png)
Step 4 - Take y term one side,
![8x=3y-xy](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jjmdp1twazabw2uxs5r0ofv8kw2fhjsxbn.png)
Step - 5 Take y common,
![8x=y(3-x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ycd8h6jnqb9vnyxehlijlo4pzinj0r2rc7.png)
Step 6 - Take x term together,
![y=(8x)/(3-x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x85j1sr036cp5md92puvc48y1qhh804e8l.png)
or
![y=f^(-1)(x)=(8x)/(3-x)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c2xepysu3p8spp8j37ndsavs7qh813rj3y.png)